Study on use of Indigenous herbal product by diabetic patient visiting diabetic centre in Nepal - Sonar, B; Jha, BN; Upadhyay-Dhungel, K (Janaki Medical College Journal of Medical Science, 2016)
Background and Objectives: Diabetes Mellitus (DM) is a chronic disease worldwide. With increasing trends towards sedentary lifestyle, the prevalence of diabetes mellitus is increasing in urban region of Nepal too. Material and Methods: A quantitative descriptive study was conducted for a period of two months. One-to-one structured interviews were taken to fill the structured questionnaire prepared after proper literature review from the patients attending a diabetic clinic in Lalitpur. The questionnaire includes the socio-demographic details, lifestyle and questionnaires related to patients’ perception and use of herbal remedies/product. Relevant information was also obtained from the patient medical files. Statistical analysis was performed by using SPSS version 20. Results: Out of total population about 30 % of people were using the indigenous product for their treatment along with allopathic medication. Among them, 17 were male and 14 were female. Various indigenous herbal products were used by the patients. Among them fenugreek, aloe Vera, bitter guard, bottle guard, black berry are the common one. The frequencies of using these products are in fig 4.4. The total percentage of patient using fen ugreek is 42%, Aleo-Vera 35%, Bittergaurd 29% and very few participants were using Bottle guard, Neem, and Hibiscus and Guava leaf too. Conclusion: Participants have good faith on use of indigenous herbal products and are using it. Fenugreeks, Aloe-Vera, Bittergourd, Neem, Bottle gourd, Hibiscus and Guava leaf are commonly used. But no consistent data regarding fixed dose or method of preparation of such product was found. So, further researches are needed to confirm the effectiveness of those indigenous products. Janaki Medical College Journal of Medical Sciences (2015) Vol. 3 (2):13-20